Agricultural investment in Iraq ( Reality and determinats ) for the period (1995-2015) - Waleed Albujari (Mesopotamia Journal of Agriculture, 2019)
This research aims to study the influence of the most important factors that reflect on the agricultural investment in Iraq (1995-2015) and its impact on the agricultural sector in general. For this, the research is based on the hypothesis that the fluctuation and decline in agricultural investment to several economic factors vary in their effect. According to this hypothesis.  The research relied on the method of linking two directions, The descriptive approach, which relied on previous studies on the same subject, quantitive, which based on the methods and styles of the standard economy, where the  ordinaryleastsquareswasusedand explanation of quantitive style results for the evaluation of the technical phase of study. Agricultural investment (fixed capital accumulation) was adopted as an approved variable, and the size of agricultural loans, inflation rate, deficit and surplus from the general budget of the government, the value of support to agricultural sector, the value of investment allocations in the agricultural sector for agricultural reclamation. The research has achieved many conclusions among which is that despite of the investment allocations directed to the agricultural sector and the initiation of the agricultural initiative in 2008 ,however, the volume of agricultural loans showed non- significant importance, no clear strategy for agricultural investment appeared , additionally, these allocations were not strongly nor directly directed to the agricultural investment, based of the above of conclusions achieved by the study on the importance of drawing or imaging a future vision of agricultural investment clear enough to get the agricultural reality really  prospered and emphasizing on the importance of of the continuity in supporting the agricultural sector specially in the increase of the investment allocations and the continuity of  the funding  policy Through. the agricultural initiative, while ensuring the existence of a strong monitoring apparatus that ensures the disbursement of these amounts in the right level in order to access agricultural investment at required level, which in turn works on the development of the agricultural sector, As well as increasing interest in the study of economic indicators and agricultural positive effects and activate the role of low-impact indicators such as support to the agricultural sector poor input support will support the outputs to improve the reality of the agricultural sector.